The impact of pollution from road runoff on lesser treefrogs, Dendropsophus minutus (Anura: Hylidae) - Benvindo-Souza, Marcelino; Araújo dos Santos, Cirley Gomes [UNESP]; Alves de Assis, Rhayane [UNESP]; Borges, Rinneu Elias; Raquel de Souza Santos, Lia; Salla, Raquel Fernanda; Luiz Cardoso Bailão, Elisa Flávia; Mendonça do Prado, Vitor Hugo (Elsevier, 2025)
Pollution from road runoff is a complex environmental issue involving a mixture of gases, hydrocarbons, metals, and plastics released by vehicles traveling along roads. In this pioneering study, male specimens of lesser treefrogs (Dendropsophus minutus) were sampled from highway margins (n = 18) and a conserved area (n = 20) in the central Cerrado region of Brazil to evaluate the ecotoxic potential of highway pollution. To this end, we applied the micronucleus test, comet assay, leukocyte profiling, histopathological analyses of the liver and gonads of anurans, as well as chemical analysis of water and collection of atmospheric particulate matter. On the highway, levels of Al, Fe, Mn, and PM2.5 exceeded the recommended limits. Frogs collected from road margins showed a significant increase in DNA damage, as evidenced by the comet assay (55% tail DNA) and the micronucleus test (622% increase) compared to frogs from the conserved area (p < 0.05). Additionally, roadside frogs exhibited a higher lymphocyte:neutrophil ratio (p < 0.05). Histological analysis of the liver revealed a lower amount of hepatic melanin in frogs from the highway area. In the gonads, frogs from highway margins had a smaller locular area, as well as reduced diameters of secondary spermatocytes and spermatogonia (p < 0.05). Overall, these results indicate that the frogs inhabiting areas adjacent to the highway were more susceptible to a range of disorders in comparison with those from protected, natural habitats, which likely reflected the increased environmental stress resulting from the runoff of pollutants produced by the traffic on the highway.
Keywords: Airborne pollution; Anurans; Comet assay; Histopathology; Micronucleus; Runoff pollution